Prolonged consumption of energy drinks does not affect the processes of memory, and increases the activity of transaminases, and cholesterol concentration – animal model study results - Nieradko-Iwanicka, Barbara; Pietraszek, Dorota; Pośnik, Katarzyna (Family Medicine & Primary Care Review, 2016)
Background . The consumption of energy drinks (ED) is popular among young people. There are concerns that it could be harmful for their health. Objectives. The aim of the study was to analyze the influence of ED consumption on animals for 30 subsequent days on memory, weight gain and biochemical parameters (alanine transaminase-ALT, asparagine transaminase-AST, creatinine, cholesterol and glycated hemoglobin-HbA1C). Material and methods . The study was conducted on 32 mice (16 females and 16 males). The mice received standard feed for rodents ad libitum. The animals were randomly assigned to four groups (8 animals each): I – female controls provided with water ad libitum, II – females provided with ED ad libitum, III – male controls provided with water, and IV – males provided with ED. Every 7 days memory retention in a passive avoidance task, and fresh spatial memory in a Y-maze were checked. The results were analyzed with Statistica 10.0. p < 0.05 was considered statistically significant. Results. The consumption of ED did not affect fresh spatial memory or memory retention in the experiment. Males drinking ED gained weight at a faster rate than control males. ED significantly increased the activity of AST in the blood sera of females and, to a lesser degree, of ALT in both males and females drinking ED. ED did not significantly affect the oncentration of creatinine or HbA1C, but significantly increased the concentration of cholesterol in the blood of males from group IV. Conclusions . The prolonged consumption of ED does not affect memory processes, but increases the activity of transaminases and cholesterol concentration in blood sera in the mice model.